(untitled) - Watkins-Goffman, Linda (New York, NY, 1990)
Thinking to Writer offers teachers a complete writing curriculum all in one text. Designed for intermediate to advanced students of English.
Keywords: English language,Report writing,English language,Tiếng Anh,Phương pháp viết báo cáo,Tiếng Anh; Textbooks for foreign speakers,Rhetoric,Tu từ học,Giáo trình dành cho người nước ngoài